Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1111/j.1365-2036.2010.04517.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomised clinical trial: efficacy of the addition of a prokinetic, mosapride citrate, to omeprazole in the treatment of patients with non-erosive reflux disease - a double-blind, placebo-controlled study

Abstract: SUMMARY BackgroundProton pump inhibitors (PPIs) are less effective in non-erosive reflux disease (NERD) patients than in reflux oesophagitis patients. Whether the addition of prokinetics to PPIs improves NERD patients' symptoms remains unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 41 publications
(83 reference statements)
2
39
1
Order By: Relevance
“…PPIs have a superior effect in terms of heartburn symptom relief than H2RAs or prokinetic drugs for the treatment of nonerosive GERD [75]. The addition of a prokinetic drug, mosapride, to omeprazole is not more effective than omeprazole alone for the treatment of non-erosive GERD [76]. Among PPIs, the treatment efficacy is not different, and the potential at the onset of GERD symptom relief during the early days of treatment might not be different, but the data are controversial [55,77,78].…”
Section: Cq: Is An Acid Suppressant Effective For the Treatment Of Gerd?mentioning
confidence: 99%
“…PPIs have a superior effect in terms of heartburn symptom relief than H2RAs or prokinetic drugs for the treatment of nonerosive GERD [75]. The addition of a prokinetic drug, mosapride, to omeprazole is not more effective than omeprazole alone for the treatment of non-erosive GERD [76]. Among PPIs, the treatment efficacy is not different, and the potential at the onset of GERD symptom relief during the early days of treatment might not be different, but the data are controversial [55,77,78].…”
Section: Cq: Is An Acid Suppressant Effective For the Treatment Of Gerd?mentioning
confidence: 99%
“…10 According to previous studies, PPI + mosapride combination therapy significantly improves ERD symptoms compared to PPI alone, but there was no major difference in the endoscopic healing rate. 11 A recent meta-analysis concluded that the combination therapy partially helps to improve QOL, but that it has no effect on alleviating symptoms or endoscopic healing.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 Adding prokinetic drugs to PPI in the treatment of GERD is recommended, due to enhancing esophageal motor function, although the efficacy is controversial. [23][24][25][26][27] PPI induced the delay of gastric emptying in solid food, but there was few literature about prevention of the treatment delayed gastric emptying, and evaluations on dyspeptic symptoms. 8,[28][29][30] Tegaserod (5-HT4 receptor agonist) was used to normalize the delayed gastric empting caused by PPIs in previous study, but tegaserod is out of market from its cardiovascular risk, so there is no proven safe drug which was studied for preventing the PPI induce delayed gastric emptying.…”
Section: Discussionmentioning
confidence: 99%